Identification of Trichoderma harzianum lip2 gene by HE-TAIL PCR - Jorge, Lurdes (2010)
Trichoderma harzianum is a widespread soil fungus, known as a biocontrol agent against soilborne plant pathogens. Its biological control against plant fungi pathogens is based on different mechanisms, namely the production of several lytic enzymes. In T. harzianum several glucanases, celulases, chitinases and proteases has been identified but little is known about its lipolytic system. The aim of this work was to achieve the complete elucidation of T. harzianum lip2 by HE-TAIL PCR (High-Efficiency Thermal Asymetric Interlaced PCR), a method described as efficient to identify flanking regions from short known DNA sequences